Transmission Structure Design and Research of Humanoid Finger based on the SMA Wire Drive - Hao Li’na; Guo Shaofei; Chen Yang (Jixie chuandong)
The shape memory alloy（SMA） actuator has many excellent properties,such as simple structure,easy to control,high power weight ratio,which makes it widely been studied in the dexterous hand as actuator.But the driving displacement is small in practical application,and need to place the drive into the arms to increase drive displacement.The module of under actuated finger structure is designed.The SMA wire worked as actuator.A novel pulley which could amplify the output displacement of actuator is designed.The permanent magnet device provided pre-stretch and restore function,which implemented the drive and transmission of one-piece lightweight design.The transmission structure of the humanoid dexterous hand is analyzed.Finally,the model of finger is made by 3D printer and assemble the single finger,implements the crawl of daily supplies.